(untitled) (Journal of actual problems of jurisprudence, 2018)
In a scientific article, the author examines in detail the problems of legal regulation of the integration of compatriots on the basis of analysis of the experience of legal systems of Germany, Poland and Kazakhstan. This paper makes recommendations for improving the legislation and its implementation. Using comparative legal analysis to identify common and specific features, advantages and disadvantages of integration issues compatriots in those countries. Keywords: compatriot, integration, legal regulation, repatriation, immigrant, foreign experience.